EVALUATION OF THE EFFECT OF PHYSICOCHEMICAL PARAMETERS ON CONCENTRATION OF MICROPLASTICS IN DAM WATERS IN KATSINA STATE, NIGERIA - Okunola, O. J; Aliyu , S; Bello, O.M (FUDMA Journal of Earth and Environmental Sciences, 2025)
Microplastics (MPs) pollution has appeared as a serious environmental and public health concern, with water systems serving as primary routes for human exposure. This study comprehensively evaluated MPs contamination across ten (10) dams in the three geopolitical zones of Katsina State, Nigeria, using a standard technique. The study determined the concentration of MPs using wet oxidation digestion methods. It analysed the surface morphology and polymer types of the samples using Scanning Electron Microscopy – Energy Dispersive X-ray (SEM-EDX) and Fourier Transform Infrared Spectroscopy (FTIR). The results revealed significant spatial variability with MPs concentrations ranging from 28.00 ± 4.00 to 48.00 ± 4.00 particles L-1. Among the dams, Zobe dam exhibited the highest Contamination Factor (CF=1.71), Polymer Risk Index (PRI=19.7), and Microplastic Pollution Risk Index (MPRI = 33.7), indicating a critical risk. The Dam samples contained five polymer types: polyethene (PE), polystyrene (PS), nylon, polyvinyl alcohol (PVA), and polyethene terephthalate (PET). Furthermore, MPs were classified into four groups based on their physical characteristics, with fragments being the most abundant, followed by fibres, films, and pellets. The estimated daily intake (EDI) of MPs was higher in children than in adults, indicating a potential health risk for consumers of these waters. The prevalence of MPs, particularly Polystyrene (PS) dominated particles at Zobe Dam, poses critical health risks, with children being disproportionately vulnerable. The study recommends immediate source reduction strategies targeting polystyrene-based products and other polymer types, establishing stringent MP monitoring programs, and developing public awareness campaigns to minimise exposure risks, especially among adults and children.